2000
DOI: 10.1002/(sici)1097-0185(20000301)258:3<235::aid-ar2>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Development of Meissner-like and Pacinian sensory corpuscles in the mouse demonstrated with specific markers for corpuscular constituents

Abstract: The development of Meissner-like and Pacinian corpuscles was studied in mice [from postnatal day (Pd) 0 to 42] by using immunohistochemistry for specific corpuscular constituents. The battery of antigens investigated included PGP 9.5 protein and neurofilaments, as markers for the central axon; S100 protein, vimentin, and p75(LNGFR) protein, to show Schwann-related cells; and epithelial membrane antigen to identify perineurial-related cells. In Meissner-like corpuscles immunoreactivity (IR) for neuronal markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…Sensory corpuscles possessing a lamellated appearance were occasionally identified in the paratendinous connective tissue. In accordance with previous studies on corpuscles in the cruciate ligament of the sheep (Halata et al 1999) and the limbs of the mouse (Albuerne et al 2000), the lamellated corpuscles exhibited central axons displaying PGP9.5 immunoreaction. The previously known corpuscles in human Section of Achilles tendinosis tendon stained for PGP9.5.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sensory corpuscles possessing a lamellated appearance were occasionally identified in the paratendinous connective tissue. In accordance with previous studies on corpuscles in the cruciate ligament of the sheep (Halata et al 1999) and the limbs of the mouse (Albuerne et al 2000), the lamellated corpuscles exhibited central axons displaying PGP9.5 immunoreaction. The previously known corpuscles in human Section of Achilles tendinosis tendon stained for PGP9.5.…”
Section: Discussionsupporting
confidence: 91%
“…9). They appeared as lamellated (Pacinian) corpuscles (e.g., Halata et al 1999;Albuerne et al 2000). The central axons showed marked PGP9.5 immunoreaction (Fig.…”
Section: Mechanoreceptors (Sensory Corpuscles)mentioning
confidence: 99%
“…We have examined peripheral innervation of MafA ϩ /Ret ϩ /GFR␣2 ϩ LTMs in the c-Maf deletion mice as well. The c-Maf Ϫ/ Ϫ mice die within a few hours of birth, when the peripheral axons have reached their targets, but have not yet fully differentiated into specialized sensory endings (Albuerne et al, 2000;Hasegawa et al, 2007). Nevertheless, we found that Pacinian corpuscles were underdeveloped in c-Maf deletion mice (Fig.…”
Section: Ltmsmentioning
confidence: 68%
“…8 PGP 9.5, nNOS, and NPY have been shown to positively stain Ab axons serving the corpuscle. 9,10 Although no previous studies have shown the estrogen receptor status of labial Pacinian corpuscles, androgen receptors have been identified in adult preputial Pacinian corpuscles. Androgen receptors were visualized in the flat fibroblast like cells of the Pacinian corpuscle.…”
Section: Discussionmentioning
confidence: 99%